Unveiling The Structures of Feeling in Ann Patchett's Tom Lake - Santoso, Yafet Kurniawan; Supsiadji, Mateus Rudi (Fakultas Ilmu Budaya Universitas 17 Agustus 1945 Surabaya, 2025)
This thesis explores how Ann Patchett’s Tom Lake captures and expresses the unspoken emotional atmosphere of rural American life during the COVID-19 pandemic through the lens of Raymond Williams’s theory of the